International Myopia Institute - Industry guidelines and ethical considerations for myopia control report - Jones, Lyndon (2019)
PURPOSE: To discuss guidelines and ethical considerations associated with the development and prescription of treatments intended for myopia control (MC).METHODS. Critical review of published papers and guidance documents was undertaken, with a view to carefully considering the ethical standards associated with the investigation, development, registration, marketing, prescription, and use of MC treatments.RESULTS. The roles and responsibilities of regulatory bodies, manufacturers, academics, eye care practitioners, and patients in the use of MC treatments are explored. Particular attention is given to the ethical considerations for deciding whether to implement a MC strategy and how to implement this within a clinical trial or practice setting. Finally, the responsibilities in marketing, support, and education required to transfer required knowledge and skills to eye care practitioners and academics are discussed.CONCLUSIONS. Undertaking MC treatment in minors creates an ethical challenge for a wide variety of stakeholders. Regulatory bodies, manufacturers, academics, and clinicians all share an ethical responsibility to ensure that the products used for MC are safe and efficacious and that patients understand the benefits and potential risks of such products. This International Myopia Institute report highlights these ethical challenges and provides stakeholders with recommendations and guidelines in the development, financial support, prescribing, and advertising of such treatments.